2020
DOI: 10.1159/000505326
|View full text |Cite
|
Sign up to set email alerts
|

Changing Patterns of Hepatocellular Carcinoma after Treatment with Direct Antiviral Agents

Abstract: <b><i>Introduction:</i></b> The impact of direct antiviral agents (DAAs) on the development of hepatocellular carcinoma (HCC) is controversial. One important aspect of this controversy is the changing pattern of HCC. <b><i>Objective:</i></b> In this study, we attempted to assess the changes in the pattern of HCC after treatment with DAAs. <b><i>Methods:</i></b> A total of 51 HCC patients after DAA treatment and 54 HCC patients without DAA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 45 publications
1
16
2
Order By: Relevance
“…On the other hand, patients who had PI for their treatment presented after a mean of seven years as shown in Table 2 . HCC was detected in a cohort for up to four years after starting DAA treatment [ 4 ]. Another study reported that cases do not show a downtrend of HCC for the first 3.6 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, patients who had PI for their treatment presented after a mean of seven years as shown in Table 2 . HCC was detected in a cohort for up to four years after starting DAA treatment [ 4 ]. Another study reported that cases do not show a downtrend of HCC for the first 3.6 years.…”
Section: Discussionmentioning
confidence: 99%
“…HCC patients after DAA treatment were found to have a significantly higher malignant portal vein invasion and local spread through malignant lymphadenopathy [9]. Another prospective study showed similar findings of significant multifocal and infiltrative HCC patterns after DAA treatment [4]. Romano et al suggested that tumor growth in patients with aggressive tumors after HCV therapy is faster and with a higher number of nodules and extra-hepatic metastases [10].…”
Section: Timingmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, no vascular invasion, lymph node metastasis, or distant metastasis was reported. Two Egyptian studies compared the HCC pattern in HCV patients without and with DAA treatment 239,240 (Table 1). Both the studies reported a higher frequency of compensated liver disease, elevated alpha‐fetoprotein, vascular invasion, and lymph node metastasis among HCC patients after DAA treatment.…”
Section: Burden Of Chronic Viral Hepatitis In Egyptmentioning
confidence: 99%
“…Recent studies which evaluated the behavior of HCC after DAAs, have found more aggressive features of HCC. For instance, a recent article by Fayoume et al found that multiplicity and infiltrative patterns were more common in DAAs-treated HCC patients compared to naïve HCC patients (13). Another study revealed that malignant PVT and lymphadenopathy were significantly more frequent in DAAstreated HCC patients (14).…”
Section: Discussionmentioning
confidence: 99%